Dinamika Kelompok Tani Lahan Kering di Kecamatan Paranggupito Kabupaten Wonogiri - Agustianingrum, Agustianingrum (Universitas Muhammadiyah Semarang, 2023)
The development of farmer groups is very important. The thing that needs to be considered in group development is group dynamics. This study aims to: (1) Determine the level of dynamics of dryland farmer groups in Paranggupito District, Wonogiri Regency and (2) analyze factors that affect the level of dynamics of dryland farmer groups in Paranggupito District, Wonogiri Regency. The research location was selected purposively in Paranggupito District, Wonogiri Regency. The sampling technique uses a multistage random sampling technique with a total sample of 47 farmer groups. Data analysis using multiple linear regression. The results showed that the level of dynamics of dryland farmer groups in Paranggupito District, Wonogiri Regency was less dynamic. Factors that have a significant influence on the level of farmer group dynamics are the leadership style of the group leader, the availability of information and the intensity of agricultural extension.